POLA PENCEMARAN Hg DAN Pb PADA FISHING GROUND DAN IKAN YANG TERTANGKAP NELAYAN : STUDI KASUS DI TELUK JAKARTA (Mercury and Lead Contamination Pattern on Fish and Fishing Ground : A Case Study in Jakarta Bay) - Mustaruddin Mustaruddin (Bumi Lestari Journal of Environment, 2013)
AbstractMercury (Hg) and lead (Pb) are two heavy metals which run-off with waste water of industry,market, and office to territorial water of Jakarta Bay. Fishing ground in adjacent water ofMarunda, Bidadari Island, and Damar Island have been contaminated by Hg and Pb.Pelagic fish caught in Jakarta Bay have not been contaminated by Hg and Pb. However,demersal fishes that have been caught in the same area, a positively contaminated with Hgand Pb. The rate of Hg and Pb in fishing ground are signicantly influence by the rate of Hgand Pb in pelagic fish (NK Hg = 0,895 at sig 0,016 and NK Pb = 0,962 at sig 0,002) and indemersal fish (NK Hg = 0,825 at sig 0,043 and NK Pb = 0,894 at sig 0,016). The pattern ofHg contamination in fishing ground to pelagic fish and demersal fish each following linearmodel Y = -0,055 + 5,314 X, and quadratic model Y = -1,370 + 215,549X – 4190,579X2, where Xrepresents rate of heavy metal in fishing ground and Y represents rate of heavy metal in fishcaught by fisherman. While pattern of Pb contamination of fishing ground to pelagic fishand demersal fish each following cubic model Y = -0,006 +1,114X - 399,652X3 and sigmoidmodel Y = e0,627 – (0,10 / X).